IMPLEMENTATION OF LOCAL WISDOM IN PRESERVING BATIK IN KARANGMALANG VILLAGE, GEBOG DISTRICT, KUDUS REGENCY - Aulia, Dinia (Universitas Negeri Semarang, 2024)
The purpose of this study was to find out local wisdom related to the preservation of batik in Karangmalang Village. The importance of this research is to provide an understanding to the public that batik wisdom in Karangmalang Village is not only implemented in the clothes that are used daily by the people but in the preservation of batik. This is also carried out on small and medium enterprises in several hamlets scattered in Karangmalang Village. With this in mind, these small businesses have an important role for the preservation of local wisdom so that this culture does not become extinct, especially since batik is one of the valuable local wisdoms for the Indonesian state. This has been designated by UNESCO as a cultural heritage of Indonesia. Besides that, batik has very diverse motifs, this makes a lot of devotees and these motifs are interesting and will not be inferior to the progress of the times.